#### Answer

slope: $=-\frac{1}{3}$
y-intercept: $(0, -3)$
Refer to the graph below.

#### Work Step by Step

Solve for $y$:
$x+3y=-9
\\x+3y-x=-9-x
\\3y=-x-9
\\\frac{3y}{3}=\frac{-x-9}{3}
\\y=-\frac{1}{3}x-3$
This means that the given equation is equivalent to $y=-\frac{1}{3}x-3$.
RECALL:
The slope-intercept form of a line's equation is $y=mx+b$ where $m$=slope and $(0, b)$ is the line's y-intercept.
Thus, the equation $y=-\frac{1}{3}x-3$ has a slope of $-\frac{1}{3}$ and a y-intercept of $(0, -3)$.
To graph the equation, perform the following steps:
(1) Plot the y-intercept $(0, -3)$.
(2) Use the slope to plot a second point.
Since the slope is $-\frac{1}{3}$, from $(0, -3)$, move 1 unit down (the rise) and 3 units to the right (the run) to reach the point $(3,-4)$. Plot $(3. -4)$.
(3) Connect the points using a straight line.
(Refer to the graph in the answer part above)